Avaliação qualitativa e quantitativa de alcalóides pirrolizidínicos derivados da monocrotalina de Crotalaria spectabilis (Fabaceae) experimentalmente tóxica para bovinos - Silva, Wuglenya Daislla Martins da (2023)
The Crotalaria spp belongs to the Fabaceae family, it is a plant used in the agricultural system as green manure and for the natural control of soil nematodes. This plant has pyrrolizidine alkaloids, substances responsible for causing poisoning in animals. Studies suggest that there is a difference in toxicity between parts of the plant, since seeds need a lower dose to cause disease and/or death in animals, compared to other parts of the plant. This work aims to evaluate qualitatively and quantitatively the pyrrolizidine alkaloids derived from monocrotaline from different parts of Crotalaria spectabilis (Fabaceae). For the execution of this work, extracts of samples of leaves, stems, flowers, pods and seeds of Crotalaria spectabilis that were experimentally toxic to cattle were produced. These extracts were evaluated via Fourier Transform Infrared Spectroscopy-FTIR, High Performance Liquid Chromatography coupled to Mass Spectrometry-HPLC/MS-ESI. From the chemical evaluations, there was a qualitative and quantitative detection of monocrotaline in all portions of the plant. Thus, it was verified that monocrotaline, monocrotaline acid and monocrotaline N-oxide are present in all studied parts of C. spectabilis, however the monocrotaline alkaloid is found in higher concentrations in the seeds.